Bimbingan Kelompok dengan Teknik Role Playing - Habsy, Bakhrudin All; Azizah, Latif Nur; Nurfirda, Ida; Fitria, Verda (TSAQOFAH, 2024)
The role playing technique in group guidance is a role playing technique that aims to solve problems by involving social relationships. The aim of this research is to help counselors and counselees in the process of solving problems by understanding each other through the social relationships they form. This research method uses library research by collecting several sources such as journals, articles, books and other sources. The research results found in the application of role playing techniques in group guidance are, the benefits of role playing techniques in group guidance, the application of role playing techniques in group guidance, the effectiveness of role playing techniques in group guidance, and obstacles to implementing role playing techniques in group guidance.